EFEKTIVITAS PENERAPAN ANGER MANAGEMENT DALAM MENINGKATKAN KEMAMPUAN MENGELOLA EMOSI MARAH PADA REMAJA LAKI-LAKI - Putu Ayu Pradnyasari; Mita Aswanti Tjakrawiralaksana (Departemen Psikologi Universitas Pendidikan Indonesia, 2021)
Anger is one of the major triggering factors in violence commited by adolescent. Anger usually become a mediator of domestic violence behavior, especially for adolescent who have problems in regulating and expressing anger. One of the interventions for reducing anger is Teen Anger Management Education (TAME), which implementing cognitive-behavioral approach. This study was aimed to investigate the effectivity of anger management group intervention based on TAME. Design of this study was quasy experimental, which involved 6 male adolescents who have high level of anger, known from their scores on the Buss-Perry Aggression Questionnaire scale, specifically on anger subscale. They were given TAME intervention which was modified into 6 sessions. It took 45-90 minutes for each session, with 3-4 days gap in between. Post-test was taken at the last session and follow-up was taken a month after the last session. Result showed that the scores from 5 out of 6 participants have been decreased statistically significant from before compared to after intervention. Therefore, it can be concluded that anger management group intervention was effective to reduce anger in the majority of participants, Z (-2.04).